Synthesis and Corrosion Resistance of FeMnNiAlC10 Multi-Principal Element Compound - Mohammed Hussien (MDPI AG, 2021)
A multi-principal element FeMnNiAlC10 bulk alloy was produced by vacuum arc melting. The same alloy was sintered as a thin film on a silicon substrate by ion beam sputter deposition. The bulk alloy has a multiphase structure the elements predominantly segregating into iron manganese carbides and nickel aluminium phases. The thin film is amorphous without detectable phase segregations. The absence of segregation is attributed to the film composition and deposition onto substrate at temperature below 400 K. The corrosion resistance of the thin film alloy was evaluated in 3.5% NaCl. The FeMnNiAlC10 thin film alloy has better corrosion resistance than 304SS. The hardness of the thin film was approximately 7.2 ± 0.3 GPa and the reduced Young’s modulus was approximately 103 ± 4.6 GPa. FeMnNiAlC10 thin film could be a good candidate for coating oil and gas extraction soft iron infrastructure.